Designing a nanostructure-based modified electrode as a biosensor for simultaneous determination of tryptophan and uric acid. Issue 2 (25th November 2014) - Ghoreishi, Sayed Mehdi; Behpour, Mohsen; Mousavi, Samira; Khoobi, Asma; Ghoreishi, Farzaneh Sadat
Abstract : Cyclic voltammograms of Trp at the surface of (a) CPE and (b) CPE-MWCNTs at pH 3.0. Abstract : A carbon paste electrode modified with multi-walled carbon nanotubes (CPE-MWCNTs) was prepared for the simultaneous determination of tryptophan (Trp) and uric acid (UA). The surface morphology of the modified electrode was characterized by scanning electron microscopy (SEM) and electrochemical impedance spectroscopy (EIS). Cyclic voltammetry (CV), chronocoulometric and differential pulse voltammetry (DPV) techniques were used to investigate the modified electrode for the electrocatalytic oxidation of Trp and UA in aqueous solutions. Using the modified electrode the separation of the oxidation peak potentials for Trp and UA was obtained to be 386.0 mV. Also the dynamic ranges for Trp and UA were achieved to be 0.6–100.0 and 0.4–100.0 μM, respectively. The detection limits ( S / N = 3) were 0.06 and 0.03 μM for Trp and UA, respectively.